2020
DOI: 10.22207/jpam.14.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Halotolerant Bacillus sp. for Mannan Degradation Isolated from Mangrove Ecosystem at Hanura Beach Lampung

Abstract: Mannose and mannooligosaccharide acted as prebiotic that consumed by probiotic bacteria. Mannanase were the second most important enzymes for the hydrolysis of hemicelluloses, beside xylanase. The objective research was to obtain eminent strains of Bacillus sp. in mannan degradation which can potentially be a probiotic candidate. The study employed a completely randomized design using four concentration levels repeated six times. Halotolerant Bacteria were isolated from mangrove ecosystem at Hanura beach, Telu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Other studies showed that Bacillus sp. as probiotic bacteria had been found in Mangrove in Lampung (Sumardi, Farisi, Ekowati, & Hairisah, 2019;Sumardi, Farisi, Ekowati, Arifiyanto, & Rahmawati, 2020).…”
Section: A Margasari Mangrovementioning
confidence: 99%
“…Other studies showed that Bacillus sp. as probiotic bacteria had been found in Mangrove in Lampung (Sumardi, Farisi, Ekowati, & Hairisah, 2019;Sumardi, Farisi, Ekowati, Arifiyanto, & Rahmawati, 2020).…”
Section: A Margasari Mangrovementioning
confidence: 99%
“…Test conducted in qualitative method and measured for enzyme index to compare. Isolate Streptomyces AB8 was used as a control (Agustina et al 2019;Arifiyanto et al 2020;Garcia-Orozco et al 2019;Rosa et al 2020;Sumardi et al 2020).…”
Section: Hydrolase Enzyme Testmentioning
confidence: 99%
“…An antifungal test was conducted on Potato Dextrose Agar media against Aspergillus IK3. Clear zones formation was observed after 24 hours of incubation at room temperature (Sumardi et al 2020).…”
Section: Antimicrobial Activitymentioning
confidence: 99%